Case report: JC polyomavirus nephropathy in simultaneous heart–kidney transplantation: the role of viral-specific in situ hybridization staining - Abu Jawdeh, Bassam G.; Smith, Maxwell L.; Hudson, Madeline R.; Mour, Girish K.; Budhiraja, Pooja; Rosenthal, Julie L. (Frontiers in Medicine, 2023)
Introduction: JC polyomavirus (JCPyV) is a ubiquitous virus that can be latent in the brain and the kidney. It is the etiologic agent responsible for progressive multifocal leukoencephalopathy, a fatal, demyelinating disease of the central nervous system, and rarely causes polyomavirus nephropathy in immunocompromised kidney transplant recipients. Case description: We present the first case of JCPyV nephropathy in a simultaneous heart-kidney transplant patient, where viral-specific in situ hybridization staining of the kidney tissue was utilized to confirm the diagnosis. The patient was diagnosed six years after simultaneous heart-kidney transplantation, and was treated with immunosuppression reduction and intravenous immunoglobulin. Discussion: JCPyV nephropathy should be considered in the differential diagnosis of kidney allograft injury, particularly, with suggestive light microscopy histologic features in absence of BK polyomavirus viremia and/or viruria. In addition to obtaining JCPyV PCR in the blood, in situ hybridization staining may have a utility in confirming the diagnosis. To date, we lack effective JCPyV-specific therapies, and prompt initiation of immunosuppression reduction remains the mainstay of treatment.